In Vitro Activity of Imipenem-Relebactam Alone or in Combination with Amikacin or Colistin against Pseudomonas aeruginosa - Asempa, Tomefa E. (Antimicrob Agents Chemother, 2019)
Relebactam is a novel class A/C β-lactamase inhibitor that restores imipenem in vitro activity against multidrug-resistant and carbapenem-nonsusceptible Pseudomonas aeruginosa. Time-kill analyses were performed to evaluate the potential role of imipenem-relebactam in combination with amikacin or colistin against P. aeruginosa. Ten clinical P. aeruginosa isolates (9 imipenem nonsusceptible) with imipenem-relebactam MICs ranging from 1/4 to 8/4 μg/ml were included. The isolates had varied susceptibilities to imipenem (1 to 32 μg/ml), amikacin (4 to 128 μg/ml), and colistin (0.5 to 1 μg/ml). Duplicate 24-h time-kill studies were conducted using the average steady-state concentrations (Css(avg)) observed after the administration of imipenem-relebactam at 500 mg/250 mg every 6 hours (q6h) alone and in combination with the Css(avg) of 25 mg/kg of body weight/day amikacin and 360 mg/day colistin in humans. Imipenem-relebactam alone resulted in 24-h bacterial densities of −2.93 ± 0.38, −1.67 ± 0.29, +0.38 ± 0.96, and +0.15 ± 0.65 log(10) CFU/ml at imipenem-relebactam MICs of 1/4, 2/4, 4/4, and 8/4 μg/ml, respectively. No synergy was demonstrated against the single imipenem-susceptible isolate. Against the imipenem-nonsusceptible isolates (n = 9), imipenem-relebactam combined with amikacin resulted in synergy (−2.61 ± 1.50 log(10) CFU/ml) against all amikacin-susceptible isolates and in two of three amikacin-intermediate (i.e., MIC, 32 μg/ml) isolates (−2.06 ± 0.19 log(10) CFU/ml). Synergy with amikacin was not observed when the amikacin MIC was >32 μg/ml. Imipenem-relebactam combined with colistin demonstrated synergy in eight out of the nine imipenem-resistant isolates (−3.17 ± 1.00 log(10) CFU/ml). Against these 10 P. aeruginosa isolates, imipenem-relebactam combined with either amikacin or colistin resulted in synergistic activity against the majority of strains. Further studies evaluating combination therapy with imipenem-relebactam are warranted.